Revealing the Tattoo Philosophy and Pop Culture of the RR Kakek Gaul Community - Lambok Hermanto Sihombing; Puji Lestari; Anna Tanaffasa; Nabilah Salwa Yusrina; Safarina Safarina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
In the current era, Indonesian people have begun to open their minds to eliminate negative thoughts about people who have tattoos on their bodies. This is due to the mixing of foreign cultures that have entered Indonesia, not even a few minors have the motivation to have tattoos on their body parts. This research analyzed one of the tattoo communities located in Jakarta named the RR Kakek Gaul Community. In order to help the researchers doing the analysis, the researchers used Semiotics concept from Roland Barthes and signs from Peirce. The sources were taken from the RR Kakek Gaul Community Instagram and YouTube accound which were more specific on two members from its community. The results of this study showed that the members of the RR Kakek Gaul Community tried to deliver messages of optimism in seeing future life and eliminating negatives from the non-tattoed people who underestimaed them. They sent those meanings through tattoo symbol they had.